Lax monitoring versus logical intuition: The determinants of confidence in conjunction fallacy. (2nd January 2016) - Aczel, Balazs; Szollosi, Aba; Bago, Bence
ABSTRACT: The general assumption that people fail to notice discrepancy between their answer and the normative answer in the conjunction fallacy task has been challenged by the theory of Logical Intuition. This theory suggests that people can detect the conflict between the heuristic and normative answers even if they do not always manage to inhibit their intuitive choice. This theory gained support from the finding that people report lower levels of confidence in their choice after they commit the conjunction fallacy compared to when their answer is not in conflict with logic. In four experiments we asked the participants to give probability estimations to the options of the conflict and no-conflict versions of the tasks in the original set-up of the experiment or in a three-option design. We found that participants perceive probabilities for the options of the conflict version less similar than for the no-conflict version. As people are less confident when choosing between more similar options, this similarity difference is proposed to serve as a mediator in the task in a way that the conflict and no-conflict conditions have their effects on confidence ratings through manipulating the similarity of the answer options.